Studies on the language and literature of the Bible : selected works of J. A. Emerton - Davies, Graham (Professor); Gordon, Robert (Professor) (Vetus Testamentum, Supplements, 2015)
John Emerton was Regius Professor of Hebrew at Cambridge University from 1968 to 1995 and is a former Editor of Vetus Testamentum and its Supplements (1975-97). His work is characterised by profound learning and rigorous argument. He published detailed articles on a wide range of subjects, not only on the Hebrew language but also on Biblical texts, Semitic philology and epigraphy, Pentateuchal criticism and other central issues in Biblical scholarship, and biographical essays on some modern scholars. The forty-eight essays in this volume have been selected to provide both an overview of Emerton's influential work in all these fields and easier access to some items which are no longer readily available.